Law Without Future : Anti-Constitutional Politics and the American Right - Jackson, Jack; Jackson, Jack (University of Pennsylvania Press, 2019)
As the 2000 decision by the Supreme Court to effectively deliver the presidency to George W. Bush recedes in time, its real meaning comes into focus. If the initial critique of the Court was that it had altered the rules of democracy after the fact, the perspective of distance permits us to see that the rules were, in some sense, not altered at all. Here was a "landmark" decision that, according to its own logic, was applicable only once and that therefore neither relied on past precedent nor lay the foundation for future interpretations. This logic, according to scholar Jack Jackson, not only marks a stark break from the traditional terrain of U.S. constitutional law but exemplifies an era of triumphant radicalism and illiberalism on the American Right. In Law Without Future, Jackson demonstrates how this philosophy has manifested itself across political life in the twenty-first century and locates its origins in overlooked currents of post-WWII political thought. These developments have undermined the very idea of constitutional government, and the resulting crisis, Jackson argues, has led to the decline of traditional conservatism on the Right and to the embrace on the Left of a studiously legal, apolitical understanding of constitutionalism (with ironically reactionary implications). Jackson examines Bush v. Gore, the post-9/11 "torture memos," the 2005 Terri Schiavo controversy, the Republican Senate's norm-obliterating refusal to vote on President Obama's Supreme Court nominee Merrick Garland, and the ascendancy of Donald Trump in developing his claims. Engaging with a wide array of canonical and contemporary political thinkers-including St. Augustine, Alexis de Tocqueville, Karl Marx, Martin Luther King Jr., Hannah Arendt, Wendy Brown, Ronald Dworkin, and Hanna Pitkin-Law Without Future offers a provocative, sobering analysis of how these events have altered U.S. political life in the twenty-first century in profound ways-and seeks to think beyond the impasse they have created.